Răspuns :
a+b+c = 163; (a+b)-c = 67; (b+c)-a = 37. 67+c+c=163 → 2c = 96 → c = 48. 37+a+a=163 → 2a=126 → a=63 → b = 163-(48+63) = 52
a + b + c = 163
( a + b ) - c = 67
( b + c ) - a = 37
( a + b ) - c = 67 ⇒ a + b = 67 + c
inlocoim in prima relatie a + b ⇒ 67 + c + c = 163 ⇒ 2c = 163 - 67 ⇒ 2c = 96 ⇒ c = 96 : 2 ⇒ c = 48
( b + c ) - a = 37 ⇒ b + c = 37 + a
inlocuim in prima relatie b + c ⇒ a + a + 37 = 163 ⇒ 2a = 163 - 37 ⇒ 2a = 126 ⇒ a = 126 : 2 ⇒a = 63
inlocuim c = 48 si a = 63 in relatia a + b + c = 163 ⇒ 63 + b + 48 = 163 ⇒ b = 163 - 111 ⇒ b = 52